"De 'conto de fadas' a 'ruptura dos guetos'" : análise da educação das relações étnico-raciais no curso de Geografia da UFMT – 2013 a 2019 - Ventura, Joilson Gonçalo (2020)
This master's research in education from the Graduate Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT) is linked to the Social Movements, Politics and Popular Education Research Line and to the Center for Studies and Research on Relations and Education (NEPRE). It investigates how the Geography course on the campus of Cuiabá, through the discipline Education of Ethnic-Racial Relations (ERER), in the period 2013 to 2019, implemented and implemented Law No. 10,639 / 2003, which provides for “History and Afro-Brazilian and African Culture ”. The guiding questions of the study consisted of: what were the obstacles and the pedagogical and institutional advances in the implementation of the discipline Education of Ethnic-Racial Relations in the Geography course? Is there a connection between the disciplines Education of Ethnic-Racial Relations with the other subjects of the course? Which points converge and diverge in this connection? The methodological approach of the research was the Case Study in which it was possible to observe, in loco, the object investigated and analyzed. To this end, the following were carried out: analyzes based on documents provided by the Course Coordination and those available on the UFMT website; the participant observation of four classes of the discipline Education of Ethnic-Racial Relations in order to understand how students act and participate in classes; and semi-structured interviews recorded in audio from the research subjects who were: students, teachers and managers. For the theoretical basis of the research we used: on Brazilian race relations we anchored mainly in Guimarães (2009), Hofbauer (2006), Domingues (2004), Paixão (2014), Seyferth (1985) and Schwarcz (1993). On affirmative actions in Siss (2003), Santos (2016) and Santos (2003); and on education and curriculum of ethnic-racial relations in Gomes (2005), Santos (2009), Costa (2013), Arroyo (2013) and Silva (2011).From the analysis of the research it was verified that the process of implantation and implementation of the discipline Education of Ethnic-Racial Relations in the Geography course represented a significant advance not only for the fulfillment of Law no 10.639 / 2003, but as a political landmark - important pedagogue in the struggle of the black Brazilian movements. However, the results indicate that there is a need for a more effective evaluation process and the inclusion of said discipline as mandatory in the Bachelor of Geography course. Thus, the implementation of Law No. 10,639 / 2003 has a long way to go until it is fully implemented at UFMT, since racism and racial inequalities are still barriers, with the need to break institutional ghettos for effective anti-racist education. The effects of the Discipline begin to arrive in basic education, since alumni work with such questions as salutary effects of anti-racist education in their training. It also reveals the need for interdisciplinary work on the part of teachers in the Geography department to fully reach the contents of anti-racist education. It is indicated that the relevant UFMT bodies should seek the institutional implementation of the aforementioned Law and of the other normative guidelines presented in the research regarding national curricular guidelines for the education of ethnic-racial relations and for the teaching of Afro- Brazilian history and culture and African.